Perlindungan Hukum terhadap Anak Dari Bahaya Perbuatan Child Grooming - Tulung, Gladys Monica; Lolong, Wenly R. J.; Runtunuwu, Yoan B. (Wajah Hukum, 2026)
This study aims to analyze regulations on child grooming and to understand and strengthen legal protection for children from the threat of sexual violence and exploitation, especially child grooming, given the increasing threat of child grooming in Indonesia. The type of research used by the author in this study is normative juridical using a statute approach. The results of the study show that cases of child exploitation originating from cyber grooming involving online media continue to rise steadily. Criminal activities in cyberspace include child sexual abuse/exploitation material, sexual extortion, sexting, live online sexual abuse, and child grooming. Child grooming itself is a process of deception used by sexual abusers to manipulate the minds of minors for the purpose of carrying out practices such as pornography, sexual violence, and indecent acts. Efforts to protect children have been made through various policies and programs to prevent violence, protect victims, and address the negative impacts caused. The Indonesian government has adopted various legal instruments and their implementing regulations to ensure the protection of children from all forms of violence.